2020
DOI: 10.3386/w27099
|View full text |Cite
|
Sign up to set email alerts
|

Health vs. Wealth? Public Health Policies and the Economy During Covid-19

Abstract: and seminar participants at UC Davis provided helpful early feedback. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 11 publications
5
96
1
3
Order By: Relevance
“…Given that earlier reopenings had no impact on consumer behavior, it is not surprising that it also had little or no downstream impact on employment. 39 These results are consistent with the findings of Lin and Meissner (2020), who use a state-border discontinuity design and find no impact of stay-at-home orders on job losses.…”
Section: Figures 11bsupporting
confidence: 72%
“…Given that earlier reopenings had no impact on consumer behavior, it is not surprising that it also had little or no downstream impact on employment. 39 These results are consistent with the findings of Lin and Meissner (2020), who use a state-border discontinuity design and find no impact of stay-at-home orders on job losses.…”
Section: Figures 11bsupporting
confidence: 72%
“…We are not the only ones studying the labor market at this time. Allcott et al (2020), Alon et al (2020), Cajner, et al (2020a [this volume]; 2020b), Chetty et al (2020), Cortes and Forsythe (2020), Dey et al (2020), Goolsbee and Syverson (2020), Gupta et al (2020), Khan et al (2020), Kurmann et al (2020), Lin and Meissner (2020), and Mongey et al (2020) all conduct exercises that are related to ours. There are surely many others that we do not cite here.…”
Section: Introductionmentioning
confidence: 69%
“…For example, Dave et al (2020) use the log of confirmed cases as the outcome in an eventstudy framework with state-specific linear trends. Lin and Meissner (2020) also use a similar event-study specification with log cases on the left-hand side. 8 These estimators can produce unexpected results when the data comes from an SIRD data-generating process.…”
Section: Other Methods Of Estimation In the Literaturementioning
confidence: 99%